SOCIO-ECONOMIC FACTORS AFFECTING VITAMIN A CASSAVA PRODUCTION IN AKINYELE LOCAL GOVERNMENT AREA OF OYO STATE, NIGERIA - OLADEJI, SOLOMON OLADELE; IGBAROOLA, AYOMIDE HANNAH; ADEKUNLE, CHIOMA PATRICIA; TOLORUNJU, ESTHER TOLUWATOPE; OYEBAMIJI, BABATUNDE ADEBAYO (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2020)
This study examines socio-economic factors affecting vitamin A cassava production in Akinyele Local Government Area of Oyo State, Nigeria. A total number of 120 respondents selected from ten (10) villages where vitamin A cassava farmers are predominantly found, they include Alabata, Ijaye, Motunde, olorisaoko, Iroko, Iwoko talontan, Ikereku, Onidundun and Akinyele communities, in all the villages twelve (12) each, vitamin A cassava was interviewed. Data were analyzed using descriptive statistics, multiple regression analysis and gross margin analysis. Results showed that majority (80%) of the farmers were male with 85.8% of the farmers married with 11.7% single, 1.7% divorced and 0.8% widowed. The average age and mean years of farming experience are 54.8 and 25.2years respectively with 10% of them having no formal education. The costs and returns to vitamin A production in the study were reflected by a mean gross margin of ₦377,675.42 and net farm income of ₦374,334.49. Results from the multiple regression analysis showed that farm size (ha) and cost of labour are statistically significant at 1% with both having positive coefficients. Cooperative participation is statistically significant at 5% with positive coefficient. The study concluded that vitamin A cassava production is a lucrative enterprise which could serve as a reliable source of income for farmers, marketers and even source of revenue to the Government. The study recommended that formation of cooperative societies should be encouraged by community leaders or extension officers in order to aid pulling of resources together.